Impress Committee Board - Sorooshian, Shahryar; M., Waris; Senthil Kumar , T.; Hasahudin, Hassan; Ida Rizyani, Tahir; Nor Sofea, Iman (FIM-UMP, 2016)
IMPRESS (Industrial Management Professional Student Society) is a representative of Faculty Student Society. This is the second batch of IMPRESS which is Batch 15/16.